2005
DOI: 10.1016/j.ejcts.2005.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear heart rate variability in CABG patients and the preconditioning effect

Abstract: The present findings show that cardiac autonomic regulation is impaired after CABG. Nonlinear HRV exponent alpha1 is a more sensitive measure to predict the postoperative outcome in CABG patients. IP alleviates the extreme autonomic reactions after surgery, suggesting that cardiac autonomic regulation is involved in the IP protective mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 24 publications
1
34
0
2
Order By: Relevance
“…However, they were in opposition to the results reported by Tseng et al [15], where the HRV parameters recorded before PCI procedure did not differ significantly from those assessed directly after the PCI procedure. Moreover, many studies have demonstrated that coronary artery bypass grafting (CABG) also leads to significant HRV reduction, which is even more pronounced than after myocardial infarction [10][11][12][13]. In addition, HRV reduction after cardiac surgery is not exclusively related to PCI or CABG, as it is also recorded in patients undergoing valve surgery [14].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, they were in opposition to the results reported by Tseng et al [15], where the HRV parameters recorded before PCI procedure did not differ significantly from those assessed directly after the PCI procedure. Moreover, many studies have demonstrated that coronary artery bypass grafting (CABG) also leads to significant HRV reduction, which is even more pronounced than after myocardial infarction [10][11][12][13]. In addition, HRV reduction after cardiac surgery is not exclusively related to PCI or CABG, as it is also recorded in patients undergoing valve surgery [14].…”
Section: Discussionmentioning
confidence: 94%
“…Studies have invariably demonstrated that coronary artery bypass grafting (CABG) also leads to significant HRV reduction [10][11][12][13]. In addition, HRV reduction after cardiac surgery is not exclusively related to PCI or CABG, as it is also recorded in patients undergoing valve surgery [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the release of local triggers of IPC activates the autonomic nervous system either directly (Schoemaker & Van Heijningen, 2000;Liem et al, 2002) or via sensory nerves (Tang et al, 1999;Xiao et al, 2001;Hu et al, 2002), and transfers the signal to the myocardium or other remote tissues. Evidence exists that sympathovagal regulation might be related to the protective mechanism of IPC (Loukogeorgakis et al, 2005;Wu et al, 2005). IPC is mediated by sympathetic neurotransmitter release and 1 -adrenergic receptor stimulation (Banerjee et al, 1993;Cohen et al, 2001).…”
Section: Heart Rate -A Measure Of Autonomic Nervous System Activitymentioning
confidence: 99%
“…Especially with the increased use of nonlinear dynamics in clinical studies Guzzetti et al 1996Guzzetti et al , 2000Voss et al 1998;Yeragani et al 2004;Kim et al 2005;Wu et al 2005;Bar et al 2007), it is important to understand the mechanisms underlying the generation of these fluctuations. However, it is becoming clear that altered nonlinear behaviour can be found in several pathologies (Wu et al 2005;Porta et al 2007a,b), although the exact contributions or importance of the nonlinear indices in these cases also need to be further investigated.…”
Section: Non-linear Controlmentioning
confidence: 99%